Implementation of green marketing concept through social media activities: A systematic literature review - Elnur Nabivi (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2020)
The last century's industrial and technological development has led to the growth of environmental problems such as global warming, climate changes, water, air, and ground pollution. The awareness of modern consumers about these issues is growing, and companies respond by using "green marketing" strategies. Green marketing refers to the development and marketing of products that are considered environmentally safe. Furthermore, the extensive use of the Internet and increasing social media's importance in recent years forced brands to communicate with consumers in this way. In this study, these two mega-trends influencing contemporary consumer behavior were combined: social media and green marketing. Although several studies explored sustainable strategies of brands in the field of social media, this body of research has not been subjected to a review. The primary goal of the research is to determine the main topics covered in the literature. A systematic literature review was conducted to take up this goal, indicating 31 relevant publications from 21 journals published between 2010 and July 2020, for exploring the ways of implementing green marketing strategies through social networks. After analyzing collected data, four main topics covered in the literature body were extracted: general marketing strategies of brands, brand promotion strategies, determinants of consumer's green purchasing behavior, and raising environmental awareness. Based on the performed synthesis, the research gaps and fruitful directions for further research were formulated.
Keywords: M30; M31; 650; green marketing; sustainability; social media; consumer behavior; systematic literature review